(3YeOI GdYQaGf aj hLhg GdbQBfs - (3eUWaj Hf YHO GdQMef GdGRejQj,J (B1155 (3g` s ((3eUQ s)
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdabjQ Edi YfGjI QHg GdCRejQj Cf LeGYI ef GdbQGA bO GdJeShG efj Cf CLeY HYV GdBjGJ GdJj GLJeY ajgG GNJdGa ef GdhLhg s
(3BNQgG (B:s
(3hCeG CHhGdbGSe HcQ Hf TGPGf aJbOe Cfg Qhi Yf JSYI QLGd s
(3GdfSNI HgG MhGTs
(3hbO aQZ GdeDda ef JCdjag HeUQ SfI (B1144 (3g`s
(3hjdjgG eNWhWI JMQjQ GdfTQ dGHf GdLRQj deUWai Hf YHOGdQMef GdCRejQj s
(3JHUQI GdYfhGf (B:s
(3LeY s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs